Unraveling the synergistic mechanism of H2SO4/H2O2 system enabled by a dynamic dosing strategy for sustainable recycling of spent Li-ion batteries - Shukai Miao; Minsheng Fu; Xinhai Li; Bichao Wu; Zhixing Wang; Guangchao Li; Xiaoping Zhou; Tao Chen; Faping Zhong; Hongbing Liu; Jiexi Wang (Hydrometallurgy, 2026)

Spatial heterogeneity and prioritization of chemical mixtures along the Yarlung Tsangpo River - Cong Wang; Xiaoping Wang; Wenyuan Su; Bao Zhu; Jie Fu; Kai Huang; Huimin Yu; Shuping Yang; Suona Zhuoga; Jianjie Fu (Water Research, 2026)

Late Quaternary palaeoenvironmental changes in the desert-oasis transitional area modulated by multiple forcings: Chronostratigraphic records from the Gurbantunggut Desert, NW China - Haoran Zong; Jingjing Chen; Deguo Zhang; Yujie Guo; Zihan Yan; Zaijun Li; Xiaoping Yang; Xiao Fu (Global and Planetary Change, 2026)

Targeted biofilm inhibition and gene expression to study the synergistic antibacterial mechanism of lauric acid and citral against Listeria monocytogenes - Menglong Liu; Haiyan Ding; Xiaoping Fu; Qiaoli Xue; Yongjin Hu (Food Research International, 2026)

Upper-crustal anisotropy in the aftershock zone of the 2021 Ms6.4 Yangbi earthquake from the S-wave splitting analysis - Fei Rao; Tuo Zheng; Haifeng Zhou; Wei Fu; Xiaoping Fan; Hui Zhang; Peng Zhang; Nan Sun (Physics of the Earth and Planetary Interiors, 2026)

Dynamic evolution of characteristic flavor molecules in Yunnan arabica coffee during roasting revealed with a multi-omics framework - Yun Niu; Xiaoping Fu; Zhuqing Zhou; Minghua Qiu; Bin Zhou; Jiangping Fan (Food Chemistry, 2026)

Deciphering the Role of Biochar on Ammonia Oxidation with Bicarbonate as an Electron Acceptor: Complete Nitrification of NH4+-N to NO3⁻-N Under Short-term Low-temperature Stress - Ruilin Wang; Jingang Huang; Jingya Liu; Huanxuan Li; Rongbing Zhou; Wei Han; Xiaobin Xu; Xiaoping Fu; Haibo Wang (Water, Air, & Soil Pollution, 2026)

Size and Geometry Effects on the Rock Mixed-Mode I/II Fracture: Insights from the Perspective of 3D Discrete Element Models - Longfei Wang; Huan Liu; Sheng Zhang; Yinan Fu; Zheng Li; Xiaoping Zhou (Rock Mechanics and Rock Engineering, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Meta Feature Disentanglement under continuous-valued domain modeling for generalizable remote sensing image segmentation on unseen domains - Chenbin Liang; Xiaoping Zhang; Wenlin Fu; Weibin Li; Yunyun Dong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Comprehensive insights into the mechanisms influencing flavor alteration in mutton soup induced by thermal and cold sterilization: Integration of flavoromics and lipidomics - Chunyuan Ping; Xiaoping Li; Tianyang Wang; Bowen Zan; Xingyou Chen; Fu Wang; Jicai Bi; Xiang Li (Food Chemistry, 2025)

Age and pedogenesis of alpine grassland soils on the northeastern Qinghai-Tibetan Plateau: Insights from optical dating - Jingjing Chen; Haoran Zong; Zihan Yan; Yujie Guo; Deguo Zhang; Xiaoping Yang; Yuxin He; Xiao Fu (CATENA, 2025)

Quantifying the spatiotemporal dynamics of urban flooding susceptibility in the greater bay area under shared socio-economic pathways using the SD-PLUS-LightGBM framework - Shiqi Zhou; Weiyi Jia; Xiwen Geng; Haowen Xu; Haifeng Diao; Zhiyu Liu; Mo Wang; Xiaoping Fu; Yuwei Wu; Renlu Qiao; Zhiqiang Wu (Resources, Conservation and Recycling, 2025)

Greenhouse gas emission reduction strategies for petrochemical wastewater treatment: Life cycle assessment of retrofitting scenarios - Xin Bao; Song Gao; Hong Yao; Xiaoping Fu; Xinyu Gao; Hui Wang; Wei Xing (Journal of Cleaner Production, 2025)

MaC14a: An AI-enhanced CRISPR-Cas14a microfluidic platform for accurate on-site detection of geminiviruses in tomato plants and whiteflies - Zhengziang Huang; Guofang Ma; Ruibin Hu; Jian Xu; Yali Fu; Jintian Tang; Dong Li; Zhijuan Chen; Xuping Shentu; Zihong Ye; Kai Sun; Xiaoping Yu (Chemical Engineering Journal, 2025)

White matter microstructural abnormalities related to emotional dysfunction and childhood trauma characterize adolescents with borderline personality disorder - Xiaoping Yi; Xueying Wang; Liying Shen; Yan Fu; Qian Xiao; Jinfan Zhang; Jun Ding; Furong Jiang; Zhejia Zhang; Alessandro Grecucci; Bihong T. Chen (Brain Imaging and Behavior, 2025)

Calculation method and application of discontinuous longitudinal deformation of shield tunnels considering variable stiffness of the ring joints - Yanbin Fu; Ning Liang; Yuehua Guo; Xiangsheng Chen; Ze Wu; Gendi Yelv; Xiaoping Li (Tunnelling and Underground Space Technology, 2025)

Multi-scale spatiotemporal patterns of urban climate effects and their driving factors across China - Panli Cai; Runkui Li; Jingxian Guo; Zhen Xiao; Haiyu Fu; Tongze Guo; Tianyi Wang; Xiaoping Zhang; Qun Xu; Xianfeng Song (Urban Climate, 2025)

Petrogenesis of the > 2.90 Ga komatiite in the Sujiagou region of the North China Craton: Implications for Archean mantle source and geodynamic setting - Rui Zuo; Xiaoping Long; Bin Wu; Mei-Fu Zhou (Precambrian Research, 2025)

A new anthraquinone derivative from the marine fish-derived fungus Alternaria sp. X112 - Xiaoyuan Xu; Gang Li; Rao Fu; Hongxiang Lou; Xiaoping Peng (Natural Product Research, 2025)

Role of autophagy in resistance to ivermectin in Haemonchus contortus - Nana Fu; Xiaoping Luo; Junyan Li; Xuezhang Zhou; Jun Du; Bintao Zhai; Anben Li; Xiaoye Yang; Yang Liu (Veterinary Parasitology, 2025)

Amorphous Cu/Fe nanoparticles with tandem intracellular and extracellular electron capacity for enhancing denitrification performance and recovery of co-contaminant suppressed denitrification - Jinming Fu; Tingting Guo; Haibo Li; Wenli Liu; Zhi Chen; Xiaoping Wang; Jianbo Guo (Bioresource Technology, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Unveiling the hidden dynamics of intermittent surface water: A remote sensing framework - Zhen Xiao; Runkui Li; Mingjun Ding; Panli Cai; Jingxian Guo; Haiyu Fu; Xiaoping Zhang; Xianfeng Song (Remote Sensing of Environment, 2024)

Modeling soil erosion dynamic processes along hillslopes with vegetation impact across different land uses on the Loess Plateau of China - Chenfeng Wang; Xudong Fu; Xiaoming Zhang; Xiaoping Wang; Ga Zhang; Zheng Gong (CATENA, 2024)

Mechanical properties and damage modeling of unloaded marble under freezing and thawing with different temperature ranges - Xiaoping Wang; Lehua Wang; Xiaoliang Xu; Hengbin Zhang; Yintao Fu; Shifu Qin (Cold Regions Science and Technology, 2024)

Liquid–liquid phase separation in Alzheimer’s disease - Qinggang Fu; Bixiang Zhang; Xiaoping Chen; Liang Chu (Journal of Molecular Medicine, 2024)

Urbanization effects on the spatial patterns of spring vegetation phenology depend on the climatic background - Peiyi Yin; Xuecao Li; Yuyu Zhou; Jiafu Mao; Yongshuo H. Fu; Wenting Cao; Peng Gong; Wanru He; Baoguo Li; Jianxi Huang; Xiaoping Liu; Zitong Shi; et al. (Agricultural and Forest Meteorology, 2024)

Modeling feedback processes between soil detachment and sediment transport along hillslopes on the Loess Plateau of China - Chenfeng Wang; Xudong Fu; Bin Wang; Zheng Gong; Ga Zhang; Xiaoping Wang (Science of The Total Environment, 2023)

4-Phenylbutyric acid may prevent mouse ovarian and uterine damage due to procymidone-induced alteration of circRNA Scar and circZc3h4 levels by controlling excessive unfolded protein response - Rui Li; Fan Li; Xuning Wang; Mingxin Bai; Hu Fu; Zhengli Yan; Xiaoping Yang; Yongfei Zhu (Pesticide Biochemistry and Physiology, 2023)

Plume effects on Martian surface: Revealing evolution characteristics of plume-surface interaction at Tianwen-1 landing site - Pengwei Luo; Xiaoping Zhang; Renrui Liu; Mingjie Zhang; Cunhui Li; Yi Xu; Roberto Bugiolacchi; Baocheng Hua; Haiyan Zhang; Liansheng Li; Jilin You; Yanyan Xu; et al. (Engineering Geology, 2023)

Optimizing the physiological pharmacokinetic model to rank the risks of persistent organic pollutants towards fish on the Tibetan Plateau - Yunqiao Zhou; Suona Zhuoga; Yan Chen; Xiaoping Wang; Jianjie Fu; Wei Zhou; Shaopeng Gao (Science of The Total Environment, 2023)

Urban agglomeration waterlogging hazard exposure assessment based on an integrated Naive Bayes classifier and complex network analysis - Mo Wang; Xiaoping Fu; Dongqing Zhang; Siwei Lou; Jianjun Li; Furong Chen; Shan Li; Soon Keat Tan (Natural Hazards, 2023)

Assessing urban flooding risk in response to climate change and urbanization based on shared socio-economic pathways - Mo Wang; Xiaoping Fu; Dongqing Zhang; Furong Chen; Ming Liu; Shiqi Zhou; Jin Su; Soon Keat Tan (Science of The Total Environment, 2023)

Geochronology of a Paleoproterozoic metamorphic complex in the Shuangsheng area of Inner Mongolia: constraints on crustal evolution - Qian Cheng; Lu Lu; Yan Wang; Junyu Fu; Rongrong Guo; Hui Zhong; Xiaoping Yang; Jiyu Du (International Geology Review, 2023)

Perfluorooctanoic acid induces tight junction injury of Sertoli cells by blocking autophagic flux - Yuan Yang; Guoqing Fu; Xueyi Zhao; Xiaoping Wu; Kaili Zhu; Shangyu Liu; Ding Yuan; Jie Wu; Ting Wang; Changcheng Zhang; Haixia Zhao (Food and Chemical Toxicology, 2023)

Occurrence, spatial heterogeneity, and risk assessment of perfluoroalkyl acids (PFAAs) in the major rivers of the Tibetan Plateau - Jiao Ren; Mengjiao Yu; Feng Chen; Liang Cui; Yuzhi Zhang; Junming Li; Mengke Chen; Xiaoping Wang; Jianjie Fu (Science of The Total Environment, 2023)

Role of Hfq in glucose utilization, biofilm formation and quorum sensing system in Bacillus subtilis - Mengyao Dong; Xingtao Yang; Lijuan Liu; Ziyao Zhou; Lei Deng; Zhijun Zhong; Haifeng Liu; Xiaoping Ma; Hualin Fu; Suizhong Cao; Liuhong Shen; Guangneng Peng (Biotechnology Letters, 2022)

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Two metabolites isolated from endophytic fungus Coniochaeta sp. F-8 in Ageratina adenophora exhibit antioxidative activity and cytotoxicity - Jie Fu; Liwen Hu; Zhen Shi; Wei Sun; Dong Yue; Ya Wang; Xiaoping Ma; Zhihua Ren; Zhicai Zuo; Guangneng Peng; Zhijun Zhong; Junliang Deng; et al. (Natural Product Research, 2021)

Physiological functions of urea transporter B - Lanying Yu; Tiantian Liu; Shuang Fu; Li Li; Xiaoping Meng; Xin Su; Zhanfeng Xie; Jiayan Ren; Yan Meng; Xuejiao Lv; Yanwei Du (Pflügers Archiv - European Journal of Physiology, 2019)
Urea transporters (UTs) are membrane proteins in the urea transporter protein A (UT-A) and urea transporter protein B (UT-B) families. UT-B is mainly expressed in endothelial cell membrane of the renal medulla and in other tissues, including the brain, heart, pancreas, colon, bladder, bone marrow, and cochlea. UT-B is responsible for the maintenance of urea concentration, male reproductive function, blood pressure, bone metabolism, and brain astrocyte and cardiac functions. Its deficiency and dysfunction contribute to the pathogenesis of many diseases. Actually, UT-B deficiency increases the sensitivity of bladder epithelial cells to apoptosis triggers in mice and UT-B-null mice develop II-III atrioventricular block and depression. The expression of UT-B in the rumen of cow and sheep may participate in digestive function. However, there is no systemic review to discuss the UT-B functions. Here, we update research approaches to understanding the functions of UT-B.

Mutation of I176R in the E coding region weakens Japanese encephalitis virus neurovirulence, but not its growth rate in BHK-21 cells - Yuyong Zhou; Rui Wu; Qin Zhao; Yung-Fu Chang; Xintian Wen; Yao Feng; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Archives of Virology, 2018)

Development and trait evaluation of chromosome single-segment substitution lines of O. meridionalis in the background of O. sativa - Ning He; Rouxian Wu; Xiaoping Pan; Liping Peng; Kang Sun; Tuo Zou; Haitao Zhu; Ruizhen Zeng; Ziqiang Liu; Guifu Liu; Shaokui Wang; Guiquan Zhang; et al. (Euphytica, 2017)

Complete genome sequence of a novel, virulent Ahjdlikevirus bacteriophage that infects Enterococcus faecium - Shaozhen Xing; Xianglilan Zhang; Qiang Sun; Jian Wang; Zhiqiang Mi; Guangqian Pei; Yong Huang; Xiaoping An; Kaifei Fu; Lijun Zhou; Baohua Zhao; Yigang Tong (Archives of Virology, 2017)

Physiological and proteomic changes in Zizania latifolia under chilling stress - Zihong Ye; Junping Liu; Ye Jin; Haifeng Cui; Xinxin An; Xianshu Fu; Xiaoping Yu (Biologia, 2017)

Forest-type shift and subsequent intensive management affected soil organic carbon and microbial community in southeastern China - Xianghua Fang; Jinchi Zhang; Miaojing Meng; Xiaoping Guo; Yanwen Wu; Xin Liu; Keli Zhao; Lizhong Ding; Yangfeng Shao; Weijun Fu (European Journal of Forest Research, 2017)

Nitrogen removal characteristics of Pseudomonas stutzeri F11 and its application in grass carp culture - Luoqin Fu; Xiaoping Zhang; Yibing Wang; Lisha Peng; Weifen Li (Fisheries Science, 2017)

Lack of association between rs10491334 in the CAMK4 gene and longevity in a Chinese population - RONG LIN; YUNXIA ZHANG; DONGJING YAN; XIAOPING LIAO; YUNXIN FU; WANGWEI CAI (Journal of Genetics, 2016)

Effect of tidal stress on fault nucleation and failure of the 2007 M s6.4 Ning’er earthquake - ChaoDi Xie; XingLin Lei; XiaoPing Wu; Hong Fu; ZiYao Xiong; XiongLin Hu; Sha Li (Science China Earth Sciences, 2016)

Nitrogen removal and water microbiota in grass carp culture following supplementation with Bacillus licheniformis BSK-4 - Quan Liang; Xiaoping Zhang; Khui Hung Lee; Yibing Wang; Kan Yu; Wenying Shen; Luoqin Fu; Miaoan Shu; Weifen Li (World Journal of Microbiology and Biotechnology, 2015)

Effect of photosynthetic bacteria on water quality and microbiota in grass carp culture - Xiaoping Zhang; Miaoan Shu; Yibing Wang; Luoqin Fu; Weifen Li; Bin Deng; Quan Liang; Wenying Shen (World Journal of Microbiology and Biotechnology, 2014)

Serine O-acetyltransferase is important, but not essential for cysteine–methionine synthesis in Fusarium graminearum - Jing Fu; Xiaoping Zhang; Xiang Chen; Yanni Yin; Zhonghua Ma (World Journal of Microbiology and Biotechnology, 2014)

Involvement of the nuclear factor-κB pathway in the adhesion of neutrophils to renal tubular cells after injury induced by neonatal postasphyxial serum - Tao Xiong; Wenbin Dong; Hui Fu; Qingping Li; Cunliang Deng; Xiaoping Lei; Lin Guo (Molecular and Cellular Biochemistry, 2014)

Bacillus subtilis SC02 supplementation causes alterations of the microbial diversity in grass carp water - Xiaoping Zhang; Luoqin Fu; Bin Deng; Quan Liang; Jiajia Zheng; Jiandong Sun; Haiyan Zhu; Lisha Peng; Yibing Wang; Shen Wenying; Weifen Li (World Journal of Microbiology and Biotechnology, 2013)

Effects of Bacillus preparations on immunity and antioxidant activities in grass carp (Ctenopharyngodon idellus) - Li Weifen; Zhang Xiaoping; Song Wenhui; Deng Bin; Liang Quan; Fu Luoqin; Zheng Jiajia; Wang yue; Yu Dongyou (Fish Physiology and Biochemistry, 2012)

P2X7 receptor expression is decreased in epithelial cancer cells of ectodermal, uro-genital sinus, and distal paramesonephric duct origin - Xin Li; Xiaoping Qi; Lingyin Zhou; Wen Fu; Fadi W. Abdul-Karim; Gregory MacLennan; George I. Gorodeski (Purinergic Signalling, 2009)

Isolation and Analysis of Cold Stress Inducible Genes in Zea mays by Suppression Subtractive Hybridization and cDNA Macroarray - Ying Zhang; Junjie Fu; Riliang Gu; Jianhua Wang; Xiaoping Chen; Jinping Jia; Jinpeng Zhang; Guoying Wang (Plant Molecular Biology Reporter, 2009)

Effects of land use on phosphorus loss in the hilly area of the Loess Plateau, China - Qinghua Meng; Bojie Fu; Xiaoping Tang; Hongchang Ren (Environmental Monitoring and Assessment, 2008)

Isolation of the maize Zpu1 gene promoter and its functional analysis in transgenic tobacco plants - Xiaoping Chen; Zhangying Wang; Riliang Gu; Junjie Fu; Jianhua Wang; Ying Zhang; Maoyan Wang; Jinpeng Zhang; Jinping Jia; Guoying Wang (Plant Cell Reports, 2007)

Isolation of a maize beta-glucosidase gene promoter and characterization of its activity in transgenic tobacco - Riliang Gu; Li Zhao; Ying Zhang; Xiaoping Chen; Juan Bao; Jinfeng Zhao; Zhangying Wang; Junjie Fu; Tingsong Liu; Jianhua Wang; Guoying Wang (Plant Cell Reports, 2006)

Control of plant growth resides in the shoot, and not in the root, in reciprocal grafts of flacca and wild-type tomato (Lysopersicon esculentum), in the presence and absence of salinity stress - Guoxiong Chen; Xiaoping Fu; S. Herman Lips; Moshe Sagi (Plant and Soil, 2003)